Pengaruh Nozzle Temperature Dan Layer Height Terhadap Akurasi Dimensi Produk Ulir Menggunakan Filamen PETG - Ferninda Putri, Sherin; Zulfitriyanto, Zulfitriyanto; Pristiansyah, Pristiansyah (Jurnal Inovasi Teknologi Terapan, 2025)
This study examines the effect of nozzle temperature and layer height on the dimensional accuracy of threaded products using Fused Deposition Modeling (FDM) technology with PETG filament material. Experiments were conducted using Taguchi method with L9 factorial design and three repetitions. The parameters tested included nozzle temperature (235°C, 240°C, 250°C) and layer height (0.10 mm, 0.15 mm, 0.20 mm) variations, with a constant print speed of 40 mm/s. The test specimen was a M16×2 6g thread with a height of 20 mm. The results show that layer height has a more significant effect than nozzle temperature on dimensional accuracy. Optimal diameter dimensional accuracy was achieved at a combination of nozzle temperature 240°C and layer height 0.15 mm with an average diameter of 15.82 mm, while optimal height dimensional accuracy was obtained at a combination of nozzle temperature 240°C and layer height 0.10 mm with an average height of 20.01 mm. This research contributes to the optimization of 3D printing process parameters for threaded products.